119 Effects of temperament on growth, plasma cortisol concentrations, and puberty attainment in Bos indicus beef heifers. (7th December 2018) - Cooke, R; Moriel, P; Cappellozza, B; Moraes Vasconcelos, J
Abstract: This experiment evaluated the effects of temperament on growth, plasma cortisol concentrations, and puberty attainment in Bos indicus beef heifers. Temperament was evaluated in 170 Nelore heifers, weaned 4 mo prior to the beginning of this experiment (d 0 to 91), via exit velocity on d 0. Individual exit score was calculated by dividing exit velocity into quintiles and assigning heifers with a score from 1 to 5 (1 = slowest; 5 = fastest heifer). Heifers were classified according to exit score as adequate (ADQ, n = 96; exit score ≤ 3) or excitable temperament (EXC, n = 74; exit score > 3). Heifer BW, BCS, and blood samples were obtained on d 0, 31, 60, and 91. Heifer exit velocity and score were recorded again on d 31, 60, and 91. Ovarian transrectal ultrasonography was performed on d 0 and 10, 31 and 41, 60 and 70, 81 and 91 for puberty evaluation. Heifer was declared pubertal at the first 10-d period in which a corpus luteum was detected. During the experiment, ADQ heifers had greater ( P < 0.01) mean BCS and BW gain, and less ( P < 0.01) mean plasma cortisol concentration compared with EXC heifers. Temperament × day interactions were detected ( P < 0.01) for exit velocity and exit score, which were always greater ( P < 0.01) in EXC vs. ADQ heifers. A temperament × day interaction was also detected ( P = 0.03) for puberty attainment, which was delayed in EXC vs. ADQ heifers. At the end of the experiment, a greater ( P < 0.01) proportion of ADQ heifers were pubertal compared with EXC heifers. In summary, B. indicus heifers classified as EXC had reduced growth, increased plasma cortisol concentrations, and hindered puberty attainment compared to ADQ heifers.